Studi Pengoptimalan Tempat Pembuangan Akhir Balang, Kabupaten Takalar - Suardi, Damayani; Fuad Aziz, Muhammad; Idris Taking, Muhammad (Journal of Urban Planning Studies, 2024)
The purpose of this research was conducted by the author to find out how to optimize the Balang landfill so that the Balang landfill is able to minimize all forms of impact caused by the existence of the landfill. The research location is in the Balang Landfill which has an area of 2.2 Ha with a Landfill of 0.7 Ha and a capacity of ± 60,000 m3. The Balang TPA is in the Balang Environment, Bontokadatto Village, South Polombangkeng District, Takalar Regency. In this study using a qualitative approach, which provides an explanation and description of the data that has been collected from the research object. The data collection process was carried out by means of direct observation, documentation and in-depth interviews with parties who had a role in the Balang TPA. Then the SWOT analysis method (Strenghs, Weaknesses, Opportunity, Threats) is used to determine how to optimize the Balang TPA. So that from the results of the analysis and observations that have been made, the authors found that the Balang TPA location is in accordance with the Takalar Regency spatial planning policy No. 6 Year 2012 which was enforced. And in terms of waste management at the Balang TPA, it already uses a controlled landfill system in accordance with Law Number 28 of 2008 in article 42 which is directed to close the TPA which is still using an open dumping system. However, in the Balang TPA location, there are problems, namely the growth of settlements around the TPA, air that is starting to be polluted, public health which is often disrupted due to bacteria and viruses, waste utilization has not been carried out, lack of counseling related to waste management, and has not implemented the waste sorting process before entering the landfill area. Therefore, for the optimization of TPA Balang based on the results of the SWOT analysis, points X and Y from the results of IFAS and EFAS are in quadrant I with values X = 0.93 and Y = 1.38. Which means the formulation of the strategy used is the SO strategy, namely utilizing the strengths possessed to get the opportunities that exist.